ChemInform Abstract: Effect of Ion Doping on the Electrochemical Performances of LiFePO4—Li3V2 (PO4)3 Composite Cathode Materials. Issue 35 (2nd September 2014) - Jin, Chao; Zhang, Xudong; He, Wen; Wang, Yan; Li, Haiming; Wang, Zhuo; Bi, Zhiying
Abstract Review: 81 refs.